Training for elite team-pursuit track cyclists - part II: a comparison of preparation phases in consecutive world-record-breaking seasons - Stadnyk, A. M. J.; Stanley, J.; Decker, T.; Slattery, K. M. (International Journal of Sports Physiology and Performance, 2024)
Purpose To compare the training characteristics of an elite team pursuit cycling squad in the 3-month preparation phases prior to 2 successive world-record (WR) performances.